DISRUPTIVE BEHAVIORS AMONG ELEMENTARY SCHOOL STUDENTS - Daviq Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
One of the negative behaviors that often appears among elementary school students is disruptive behavior. Symptoms of disruptive behaviors are the behaviors related to learning activities, the behaviors that interfere with students' rights in learning, psychologically and physically unsafe behaviors, and the behaviors that cause property damages at schools. This article aims to provide insightful knowledge, especially for parents and teachers, about disruptive behavior and understand it so that parents and teachers can reinforce it and the children avoid disruptive behavior. The research method in this article is a literature review. This article contains definitions, causes, and symptoms of disruptive behavior. In addition, this article provides some solutions and tips for teachers and parents on how to deal with children who behave disruptively. One of the strategies to deal with disruptive behavior is guidance and counseling services based on a developmental approach. There are several forms of intervention to overcome disruptive behavior that practitioners of clinical and developmental therapy have carried out with different target focuses, namely on children, parents, and the environment. These interventions are necessary so that the opportunity to take advantage of childhood development can be appropriately realized.